(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Over the last decade, the rapid development of the oil and gas industry has been accompanied by significant environmental challenges. Drilling muds, petroleum products, and chemical reagents generated during oil and gas extraction processes adversely affect soil, water, and atmospheric quality. This research investigates the chemical composition, toxicological risks, and integrative eco-safe technologies for drilling muds. The study applies a combined physicochemical and biological approach to reduce environmental hazards and enable secondary utilization of wastes as valuable resources. The results demonstrate that multi-method strategies significantly enhance environmental safety while contributing to sustainable industrial practices.